Antibacterial activity and mode of action of ferulic and gallic acids against pathogenic bacteria - Anabela Borges (2013)
The increased resistance of pathogenic microorganisms is frequently attributed to the extreme and inadequate use of antibiotics and transmission of resistance within and between individuals. To counter the emergence of resistant microorganisms, considerable resources have been invested in the search for new antimicrobials. Plants synthesize a diverse array of secondary metabolites (phytochemicals) known to be involved in defense mechanisms, and in the last few years it is recognized that some of these molecules have health beneficial effects, including antimicrobial properties. In this study, the mechanism of action of gallic (GA) and ferulic (FA) acids, a hydroxybenzoic acid and a hydroxycinnamic acid, was assessed on Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Listeria monocytogenes. The targets of antimicrobial action were studied using different bacterial physiological indices: minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), membrane permeabilization, intracellular potassium release, physicochemical surface properties, and surface charge. It was found that FA and GA had antimicrobial activity against the bacteria tested with MIC of 500 mu g/mL for P. aeruginosa, 1500 mu g/mL for E. coli, 1750 mu g/mL for S. aureus, and 2000 mu g/mL for L. monocytogenes with GA; 100 mu g/mL for E. coli and P. aeruginosa, 1100 mu g/mL and 1250 mu g/mL for S. aureus and L. monocytogenes, respectively, with FA. The MBC for E. coli was 2500 mu g/mL (FA) and 5000 (GA), for S. aureus was 5000 mu g/mL (FA) and 5250 mu g/mL (GA), for L. monocytogenes was 5300 mu g/mL (FA) and 5500 mu g/mL (GA), and 500 mu g/mL for P. aeruginosa, with both phytochemicals. GA and FA led to irreversible changes in membrane properties (charge, intra and extracellular permeability, and physicochemical properties) through hydrophobicity changes, decrease of negative surface charge, and occurrence of local rupture or pore formation in the cell membranes with consequent leakage of essential intracellular constituents. The overall study emphasizes the potential of plant-derived molecules as a green and sustainable source of new broad spectrum antimicrobial products.